Developing open disclosure strategies to medical error using simulation in final-year medical students: linking mindset and experiential learning to lifelong reflective practice. (3rd December 2020) - Lane, Andrew Stuart; Roberts, Christopher
Abstract : Introduction and objectives: Open disclosure is a policy outlining how healthcare practitioners should apologise for mistakes, discussing them with the harmed parties. Simulation is a training and feedback method in which learners practise tasks and processes in lifelike circumstances. We explore how final-year medical students experience the learning of open disclosure. Methods: A qualitative study of final-year medical students who had been involved a high-fidelity simulation session based on open disclosure after medication error was conducted. Students were selected using purposive sampling. Focus groups illuminated their experiences and interpretation of simulated open disclosure experiences. The data were analysed using interpretative phenomenological analysis and supported two superordinate themes: (1) identifying learning needs; and (2) learning to say sorry Results: The medical students constructed their learning in three different ways: negotiating environmental relationships; embracing challenge and stress; and achieving learning outcomes. The data reinforced the need for psychological safety, emphasised the need for emotional arousal and demonstrated the need for both individual and collective reflective learning. Our data linked the benefits of experiential learning to the development of growth mindset and Jarvis's theory. Conclusions: The lived experience of the final-year medical student participants in this study reinforced the notions of continuous psychological safety and the need for emotional arousal during learning. Our data also demonstrated the variety of participant experiences when preparing to give open disclosure, reinforcing the need for facilitators to optimise learning for the whole group as well as the individuals, given that participants are at different parts of their learning cycle.